Herpes zoster infection of maxillary nerve: A case report - Isha Thakur; Basavaraj Shilpa; Hanumantha Bandalore Satheesha Reddy; Sri Krishna Koppula (Wolters Kluwer Medknow Publications, 2017)
Herpes zoster of the trigeminal nerve branches caused by varicella zoster is a clinical entity consisting of erythematous macules, papules, vesicles, bullae, small ulcers and erythematous plaques, with characteristic short acute/pre-eruptive phases and long herpetic periods with pain. It is caused by reactivation of latent varicella infection. Herpes zoster is a less common endemic disease compared to varicella. During the prodromal stage, the only presenting symptom may be odontalgia, which may prove to be a diagnostic challenge for the dentist. Emergency treatment for a misdiagnosis such as trigeminal neuralgia, odontalgia, and acute pulpitis, as well as complications reported in literature such as tooth resorption, periapical lesions, periodontal destructions, and osteomyelitis may cause an irreversible damage to the patient. Hence, the dentist must be familiar with the presenting signs and symptoms in prodrome of herpes zoster infection of trigeminal nerve. The present article focuses on the pathogenesis, clinical picture, difficulties in diagnosis and management of such cases.